(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article provides information about the participation of Uzbek female athletes in sports events at the former Soviet level during the Soviet era. Uzbek female athletes actively participated in competitions within the former Soviet Union in the second half of the last century. In the early years, the results were unsatisfactory for various reasons, but later the indicators improved. These results allowed Uzbek female athletes to participate in world-class tournaments as part of various teams of the former Soviet Union.